Kepuasan Pengguna: Peran Pengetahuan Produk dan Pengalaman Konsumen pada Kualitas Produk, Kualitas Layanan dan Citra Merk - Suryowati Suryowati (Journal of Business Management Education (JBME), 2023)
The goal of this study was to find out how product quality, service quality, and brand image directly affect user satisfaction and how product knowledge and consumer experience indirectly affect user satisfaction through product quality, service quality, and brand image.The research method used is a quantitative one; data was obtained by distributing questionnaires to respondents and then processed using SmartPLS 3.0. The sample used in this study was 260 respondents who were BPJS Employment users in the non-formal sector. The results showed that product and service quality had a positive and significant effect on user satisfaction, while brand image had no effect. Consumer experience mediates the effect of product quality and service quality but does not mediate the effect of brand image on user satisfaction. Product knowledge does not mediate product quality, service quality, or brand image. Based on the research results, BPJS Employment can develop strategies that are relevant to the research results, namely focusing more on improving the quality of products and services to improve the consumer experience, thereby creating consumer satisfaction.